(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
This article examines the significant impact of deforestation on climate change, exploring the complex interactions between forest ecosystems and the Earth’s climate system. It delves into the mechanisms through which deforestation contributes to greenhouse gas emissions, alters regional climate patterns, and exacerbates global warming. Additionally, the article discusses the socio-economic drivers of deforestation, including agricultural expansion, logging, and infrastructure development, and their implications for forest conservation and climate mitigation efforts. By synthesizing scientific research and empirical evidence, the article aims to elucidate the critical role of forests in regulating the Earth’s climate and underscore the importance of addressing deforestation as a key strategy for climate change mitigation and adaptation.